NAG-1/GDF15 prevents obesity by increasing thermogenesis, lipolysis and oxidative metabolism - Chrysovergis, Kali (2014)
OBJECTIVE: Obesity is a major health problem associated with high morbidity and mortality. NSAID activated gene, (NAG-1) is a TGF-β superfamily member reported to alter adipose tissue levels in mice. We investigated whether hNAG-1 acts as a regulator of adiposity and energy metabolism. DESIGN/SUBJECTS: hNAG-1 mice, ubiquitously expressing hNAG-1, were placed on a control or high fat diet (HFD) for 12 weeks. hNAG-1 expressing B16/F10 melanoma cells were used in a xenograft model to deliver hNAG-1 to obese C57BL/6 mice. RESULTS: As compared to wild-type littermates, transgenic hNAG-1 mice have less white fat and brown fat despite equivalent food intake, improved glucose tolerance, lower insulin levels and are resistant to dietary- and genetic-induced obesity. hNAG-1 mice are more metabolically active with higher energy expenditure. Obese C57BL/6 mice treated with hNAG-1 expressing xenografts show decreases in adipose tissue and serum insulin levels. hNAG-1 mice and obese mice treated with hNAG-1 expressing xenografts show increased thermogenic gene expression (UCP1, PGC1α, ECH1, Cox8b, Dio2, Cyc1, PGC1β, PPARα, Elvol3) in brown adipose tissue (BAT) and increased expression of lipolytic genes (Adrb3, ATGL, HSL) in both white adipose tissue (WAT) and BAT, consistent with higher energy metabolism CONCLUSION: hNAG-1 modulates metabolic activity by increasing the expression of key thermogenic and lipolytic genes in BAT and WAT. hNAG-1 appears to be a novel therapeutic target in preventing and treating obesity and insulin resistance.